Organizational Commitment as A Predictor of Job Performance in Hospital Employees - Trisnawati, Ika; Harahap, Farida; Farida, Haniek (World Psychology, 2025)
Low Organizational Commitment has the potential to reduce the level of employee Job Performance in the Hospital environment. This study aims to analyze the effect of Organizational Commitment on employee Job Performance at RSU Kharisma Paramedika. This study uses a quantitative approach with a correlational research type. Participants in this study were 128 employees of RSU Kharisma Paramedika. The data collection technique used a questionnaire with a Likert scale. The instrument used in the Job Performance variable is a modification of the IWPQ Koopmans et al. (2016) and in the Organizational Commitment variable using a modification of the OCQ Mowday et al. (1982). The validity test of the instrument uses the Gregory and Product Moment formulas and the reliability test uses Alpha Cronbach. Data analysis uses simple linear regression analysis with the help of SPSS 25 software. The results of the study show that: (1) Organizational Commitment can be a predictor of Job Performance of employees of RSU Kharisma Paramedika. (2) Organizational Commitment can be a predictor of task performance of employees at Kharisma Paramedika Hospital. (3) Organizational Commitment can be a predictor of contextual performance in employees at Kharisma Paramedika Hospital. (4) Organizational Commitment cannot be a predictor of counterproductive work behavior in employees at Kharisma Paramedika Hospital.